EFFECT OF NEEM-BASED FORMULATIONS (NIMBECIDINE AND ULTINEEM) ON THE SPAWNING SUCCESS OF ZEBRAFISH DANIO RERIO (CYPRINIDAE) - PURUSHOTTAM K. SINGH; BADRE ALAM ANSARI (The Bioscan, 2010)
Present research work was based on the evaluation of the toxic effects of two Neem-based pesticides viz. Nimbecidine and Ultineem on the reproductive ability of zebrafish. Four month old zebrafish (both male and female) were exposed to 96-h LC5 values (0.27μg/L for Nimbecidine and 0.08μg/L for Ultineem) for one month. Fishes were brought back to normal water and allowed to breed to observe the fecundity and hatchability. Results show significant reduction in fecundity and hatchability as compared to that of control. It was observed that the fecundity was reduced by 21% in Nimbecidine and 37.77% in Ultineem treated fishes. A significant decrease in hatchability up to 21.69% in Nimbecidine and 26.99% in Ultineem treated fishes were observed respectively. The number of unhatched/dead eggs in treated fishes increased significantly (p<0.05 for each case). The results suggest that low concentrations (96-h LC5 values) of both the pesticides may have a significant effect on the reproduction of zebrafish.